Managing fiscal decentralization - Ahmad, Ehtisham; Tanzi, Vito (Routledge studies in the modern world economy, 2002)
The growth of interest in fiscal decentralization has meant that there has been something of a rush to enshrine this in policy - The World Bank has reported that about 70 countries see this as a major part of their development strategy. This book critically examines the case for decentralization. This collection of contributions comes from a world-wide team of experts, including Albert Breton, Piero Giarda and Anwar Shah.